Penegakan Hukum Dalam Pengadaan Barang/Jasa Pemerintah Menurut Perpres Peraturan Presiden Nomor 12 Tahun 2021 Tentang Perubahan Atas Peraturan Presiden Nomor 16 Tahun 2018 Tentang Pengadaan Barang /Jasa Pemerintah.(Studi Kasus Putusan Pttun Surabaya Nomor - Muhammad Fahruddin (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2023)
The government has made many efforts to improve the quality of human resources, one of which is by procuring government goods and services by government agencies. The State of Indonesia is a legal country that is developing (developing country), which is currently actively carrying out development in all fields. Development is an effort to create prosperity and welfare of the people. Procurement that uses providers of goods and services, both as business entities and individuals, is basically carried out through the selection of providers of goods and services. Procurement of government goods and services by direct procurement is carried out by procurement officials by buying goods or paying for services directly to providers of goods and services, without going through a tender or selection process. In essence, direct procurement is normal, where between providers who have procurement goods and services that require goods and services there is an agreement to conduct a tender for goods and services at a certain price.